Trastorno de conducta alimentaria y depresión en los estudiantes del Instituto Tecnológico Superior Sudamericano - Rada Torrez, Faryd Anthony Alexander (2023)
Eating disorders (ED) and depression are considered serious mental illnesses that affect millions of people around the world and have repercussions in the personal, family and social spheres. The purpose of this research was to describe eating disorders and depression according to sex and age group in students of the Instituto Tecnológico Superior Sudamericano in the city of Loja during April 2021 - March 2022. The study had a quantitative approach, and a crosssectional cohort, with a sample of 151 participants, made up of 74.17% male and 25.83% female, who were used the Eating Attitude Test 26 (EAT 26) tool for eating disorder and the Zung Scale to measure depression. Obtaining a high prevalence of not suffering from eating disorder in 36.42% (n=55) men and 11.92% (n=18) women from 18 to 22 years of age. The degree of mild depression prevailed in 19.21% (n=29) of the male population and 6.62% (n=10) of the female population between the ages of 18 and 22. The relationship between mild depression and risk of eating disorder in students was evidenced with 12.58% (n=19), however, it was not enough to demonstrate a statistically significant association when performing the chi2 hypothesis test where x2 calculated = 4.199 is less than critical x2 = 7.815, with a p value > 0.05 concluding that both variables are independent